Hepatitis delta virus: replication strategy and upcoming therapeutic options for a neglected human pathogen - Lempp, Florian A.; Urban, Stephan (Viruses, 2017)
The human Hepatitis Delta Virus (HDV) is unique among all viral pathogens. Encoding only one protein (Hepatitis Delta Antigen; HDAg) within its viroid-like self-complementary RNA, HDV constitutes the smallest known virus in the animal kingdom. To disseminate in its host, HDV depends on a helper virus, the human Hepatitis B virus (HBV), which provides the envelope proteins required for HDV assembly. HDV affects an estimated 15-20 million out of the 240 million chronic HBV-carriers and disperses unequally in disparate geographical regions of the world. The disease it causes (chronic Hepatitis D) presents as the most severe form of viral hepatitis, leading to accelerated progression of liver dysfunction including cirrhosis and hepatocellular carcinoma and a high mortality rate. The lack of approved drugs interfering with specific steps of HDV replication poses a high burden for gaining insights into the molecular biology of the virus and, consequently, the development of specific novel medications that resiliently control HDV replication or, in the best case, functionally cure HDV infection or HBV/HDV co-infection. This review summarizes our current knowledge of HBV molecular biology, presents an update on novel cell culture and animal models to study the virus and provides updates on the clinical development of the three developmental drugs Lonafarnib, REP2139-Ca and Myrcludex B.
Gesehen am 10.08.2018
This article belongs to the Special Issue "Recent Advances in Hepatitis B Virus Research"